Pharmacokinetics of Tinidazole in Chinese subjects: Comparison of Mongolian, Korean, Hui, Uighur and Han nationalities - Xin-Yu Chang; Tao Guo; Dong-Ya Xia (Frontiers Media S.A., 2009)
ABSTRACT - Purpose. This study investigated the pharmacokinetics of tinidazole in subjects of five different Chinese nationalities (Han, Mongolian, Korean, Hui, and Uighur). Methods. Fifty healthy subjects (five male and five female of each nationality) were recruited for the study, and each received 1 g tinidazole. A total of 14 blood samples were collected over a 72-hour period after administration. Results. Pharmacokinetic profiles, including area under the curve from time zero to infinity (AUC0-inf), peak plasma concentration (Cmax), time to reach Cmax (tmax), oral clearance (CL/F), elimination rate constant (Ke), and elimination half-life (t1/2), were determined following a single oral dose of tinidazole. The respective pharmacokinetic properties of Han, Mongolian, Korean, Hui, and Uighur nationalities were: half-life (h): 16.94±2.40, 16.40±1.79, 16.63±1.82, 16.81±1.56, 14.34±1.92; Cmax (μg/mL): 19.04±2.42, 19.22±4.93, 20.83±3.33, 20.25±4.05, 18.81±3.10; AUC0-inf (h•μg/mL): 483.13±65.65, 479.70±99.74, 511.07±53.47, 514.25±130.78, 388.58±37.37. The t1/2 and AUC0-inf of Uighur subjects were significantly lower (p =0.023, 0.011) and the CL/F and Ke were significantly higher (p = 0.003, 0.013) than those of other nationalities. After normalization by weight, the differences in AUC0-inf and CL/F between Uigur subjects and those of other races were still significant. Conclusions. The results indicate that ethnicity had significant impact on the pharmacokinetics of tinidazole after a single oral dose in healthy volunteers of different nationalities in China.